2009
DOI: 10.1103/physreve.79.036107
|View full text |Cite
|
Sign up to set email alerts
|

Stabilization of multiarmed spiral waves by circularly polarized electric fields

Abstract: The influence of circularly polarized electric fields (CPEFs) on the stability of multiarmed spiral waves is investigated. It is shown that CPEFs can change the period of the multiarmed spirals. The average period is an important quantity of multiarmed spiral and it must be larger than a threshold for stable multiarmed spiral. After a counter-rotating CPEF with suitable amplitude and period is applied, the average period of the multiarmed spiral may increase, which stabilizes the multiarmed spiral.

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3

Citation Types

0
4
0

Year Published

2011
2011
2024
2024

Publication Types

Select...
8

Relationship

1
7

Authors

Journals

citations
Cited by 14 publications
(4 citation statements)
references
References 41 publications
0
4
0
Order By: Relevance
“…Multiarmed spiral wave could be developed from a group of broken waves only when the distances among the tips are less than a wave lengthen, and the these spiral segments rotate in the same direction [13]. Multiarmed spiral waves are unstable in the media with high excitability but these waves could be stabilized by imposing external field on the media [63].…”
Section: Introductionmentioning
confidence: 99%
“…Multiarmed spiral wave could be developed from a group of broken waves only when the distances among the tips are less than a wave lengthen, and the these spiral segments rotate in the same direction [13]. Multiarmed spiral waves are unstable in the media with high excitability but these waves could be stabilized by imposing external field on the media [63].…”
Section: Introductionmentioning
confidence: 99%
“…[9][10][11][12][13][14][15][16] The emergence of spiral wave in cardiac tissue is regarded as harmful, thus many schemes have been proposed to suppress the spiral wave and turbulence, and the dynamical mechanism of control scheme becomes important. Particularly, it has been confirmed that circularly polarized electric fields 17,18 can be very effective to suppress spiral wave, or stabilize the multi-armed spiral waves in reaction-diffusion systems. Furthermore, it is much attractive to explore the potential mechanism of unpinning spiral wave 19 driven by series of stimuli in reaction-diffusion systems.…”
Section: Introductionmentioning
confidence: 98%
“…Both dc and ac electric fields can induce the drift of spirals [24][25][26][27]. Recently, a circularly polarized electric field (CPEF) has been proposed theoretically [28,29], and the drift of spiral waves under the influence of such an electric field is studied numerically. By applying two ac electric fields perpendicular to each other with four electrodes (see Fig.…”
Section: Introductionmentioning
confidence: 99%